Autoantibodies and Liver Disease: Uses and Abuses - Marilyn V Zeman; Gideon M Hirschfield (Canadian Journal of Gastroenterology)
Confirming whether a patient has autoimmune liver disease is challenging, given its varied presentation and complex definitions. In the continued absence of pathognomonic serum markers, diagnosis requires evaluation of laboratory investigations and, frequently, a liver biopsy – all of which need to be interpreted in the correct clinical context, with an emphasis on exclusion of viral infections, drug toxicity and metabolic disease. However, clear diagnosis is important for appropriate and timely therapy. Autoantibodies remain important tools for clinicians, and were the first proposed serological markers to aid in differentiating viral from chronic autoimmune hepatitis. Their presence is occasionally considered to be synonymous with autoimmune liver disease – a misinterpretation of their clinical significance. The present article summarizes the serum autoantibodies currently investigated in clinical and research practice, along with a description of their value in adult chronic liver diseases, with an emphasis on their appropriate use in the diagnosis and management of patients with autoimmune liver disease.